2009
DOI: 10.1111/j.1752-699x.2009.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Sputum dipalmitoylphosphatidylcholine level as a novel airway inflammatory marker in asthmatic children

Abstract: Elevated DPPC levels are evident in induced sputum of all asthmatic children and they are significantly related to sputum ECP levels and pulmonary function test parameters. Nevertheless, the value of DPPC estimation in the clinical management of children with asthma remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…WRIGHT et al [21] observed that the proportion of PC32:0 was decreased in sputum, but not in BAL in patients with asthma, while CHANG et al [22] found that PC32:0 correlated with eosinophilic cationic protein in sputum of children with asthma. It has also been observed that children with asthma have higher levels of PC32:0 in sputum compared with control subjects [23]. In atopic asthma, experimental antigen exposure has been shown to induce a reduction in PG in large surfactant aggregates collected from BAL [24].…”
Section: Discussionmentioning
confidence: 89%
“…WRIGHT et al [21] observed that the proportion of PC32:0 was decreased in sputum, but not in BAL in patients with asthma, while CHANG et al [22] found that PC32:0 correlated with eosinophilic cationic protein in sputum of children with asthma. It has also been observed that children with asthma have higher levels of PC32:0 in sputum compared with control subjects [23]. In atopic asthma, experimental antigen exposure has been shown to induce a reduction in PG in large surfactant aggregates collected from BAL [24].…”
Section: Discussionmentioning
confidence: 89%
“…However, FVC has previously been noted to negatively correlate with outdoor and indoor environmental exposures in children [ 44 – 47 ] and adults [ 48 ]. FVC in children has also been negatively correlated with various biomarkers including airway macrophage carbon content [ 45 ], exhaled breath malondialdehyde [ 46 ] and sputum dipalmitoylphosphatidylcholine [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neither bronchoalveolar lavage (BAL) nor induced sputum appears to be optimal to determine their concentrations in ELF. Induced sputum is performed only in specialized centers and successful only in 30–40% of the cases with particularly low success rates in healthy individuals that produce little sputum [76]. DPPC levels measured in induced sputum were 49.3 ± 20.1 ”g/mL in healthy children.…”
Section: Particle Action In the Deep Lungmentioning
confidence: 99%
“…DPPC levels measured in induced sputum were 49.3 ± 20.1 ”g/mL in healthy children. As DPPC represents ~50% of total phospholipids, the concentration of phospholipids would be 0.1 mg/mL [76]. BAL has repeatedly been used for qualitative and quantitative measurement of protein and lipid levels of the ELF.…”
Section: Particle Action In the Deep Lungmentioning
confidence: 99%